From Bench to the Clinic: The Path to Translation of Nanotechnology-Enabled mRNA SARS-CoV-2 Vaccines - Lopez‑Cantu, Diana O.; Wang, Xichi; Carrasco‑Magallanes, Hector; Afewerki, Samson; Zhang, Xingcai; Bonventre, Joseph V.; Ruiz‑Esparza, Guillermo U. (Nano-Micro Letters, 2022)
During the last decades, the use of nanotechnology in medicine has effectively been translated to the design of drug delivery systems, nanostructured tissues, diagnostic platforms, and novel nanomaterials against several human diseases and infectious pathogens. Nanotechnology-enabled vaccines have been positioned as solutions to mitigate the pandemic outbreak caused by the novel pathogen severe acute respiratory syndrome coronavirus 2. To fast-track the development of vaccines, unprecedented industrial and academic collaborations emerged around the world, resulting in the clinical translation of effective vaccines in less than one year. In this article, we provide an overview of the path to translation from the bench to the clinic of nanotechnology-enabled messenger ribonucleic acid vaccines and examine in detail the types of delivery systems used, their mechanisms of action, obtained results during each phase of their clinical development and their regulatory approval process. We also analyze how nanotechnology is impacting global health and economy during the COVID-19 pandemic and beyond. Highlights: 1 Pfizer–BioNTech’s and Moderna’s nanotechnology-enabled mRNA vaccines are the first of its kind to be approved for human use. 2 The COVID-19 pandemic has changed our lives and although SARS-CoV-2 has caused irreversible health, social and economic damage, continuous and extensive efforts world-wide were essential to reduce its deleterious effects.